PENGARUH KOMPETENSI, ETIKA KERJA DAN IKLIM ORGANISASI TERHADAP KINERJA GURU MAN 3 BANYUWANGI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Susanto, Fidy Deli; Wahyuni, Ika; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
The purpose of the study was to determine the Influence of Competence, Work Ethics and Organizational Climate on the Performance of MAN 3 Banyuwangi Teachers with Job Satisfaction as an Intervening Variable. The sampling technique used in this study was simple random sampling of 45 people. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, showed that Competence has a positive and significant effect on Job Satisfaction, Work ethic has a positive and significant effect on Job Satisfaction, Organizational climate has a positive but not significant effect on Job Satisfaction, Competence has a positive and significant effect on Teacher Performance, Work ethic has a negative but not significant effect on Teacher Performance, Organizational climate has a positive but not significant effect on Teacher Performance, Job satisfaction has a positive and significant effect on Teacher Performance, Competence has a positive and significant effect on Teacher Performance through Job Satisfaction, Organizational culture has a positive but not significant effect on Teacher Performance through Job Satisfaction, Organizational climate has a positive but not significant effect on Teacher Performance through Job Satisfaction